2019
DOI: 10.1159/000500399
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vonoprazan for 48-Week Maintenance Therapy of Patients with Healed Reflux Esophagitis

Abstract: Aims: We aimed to evaluate the efficacy of vonoprazan (VPZ) as maintenance therapy for healed reflux esophagitis (RE). Methods: We enrolled 74 patients diagnosed with RE with frequency scale for the symptoms of gastroesophageal reflux disease (FSSG) total score ≥8 after at least 8 weeks of treatment with standard proton pump inhibitors (PPIs). These patients were switched to VPZ 20 mg for 4 weeks. We also enrolled 71 patients with no endoscopic evidence of erosive esophagitis who received maintenance therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Maintenance therapy with vonoprazan 10 mg once daily prevented the relapse of oesophageal mucosal breaks in 86.0% of EO patients. 33 The efficacy and safety of keverprazan, in the long run, need to be clarified. Lastly, serum gastrin levels were not monitored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance therapy with vonoprazan 10 mg once daily prevented the relapse of oesophageal mucosal breaks in 86.0% of EO patients. 33 The efficacy and safety of keverprazan, in the long run, need to be clarified. Lastly, serum gastrin levels were not monitored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 24-week 10-mg-vonoprazan maintenance period, the symptomatic non-relapse rates for acid reflux-associated and dysmotility symptom FSSG scores were 86.5 and 80.8%, respectively [6]. During the 48-week 10-mg-vonoprazan maintenance therapy, the symptomatic non-relapse rates for acid reflux-related symptom score of FSSG and acid reflux score of the Gastrointestinal Symptom Rating Scale at 48 weeks were 70.0 and 72.0%, respec- tively [15]. In another study, no significant difference was noted in the FSSG score between 8 and 52 weeks of 10-mg VPZ administration [16].…”
Section: Gerd Symptomsmentioning
confidence: 99%
“…In 5 open-label prospective studies, vonoprazan 10 mg once daily showed effective 8-week [11], 24-week [6], 48- week [15], and 52-week [13,16] maintenance therapy of healed reflux oesophagitis or erosive oesophagitis refractory to PPIs [6,11,13,15,16]. On-demand therapy using 20-mg vonoprazan tablets is also an effective alternative maintenance therapy for mild reflux esophagitis [17].…”
Section: Efficacy Of Maintenance Therapymentioning
confidence: 99%
“…Considering vonoprazan as maintenance therapy, a total of 4 studies were included in the analysis [22][23][24][25]. Table V shows information about treatment-emergent adverse events, while several adverse events with frequency > 5% reported in the studies are described in Table VI.…”
Section: Vonoprazan Use As Maintenance Therapymentioning
confidence: 99%
“…The great variability observed across the studies' estimates is related to whether the treatment was an initial or a maintenance therapy. Regarding serious adverse events, the occurrence ranged from 0.0% to 16.3% and from 0.0% to 2.0% for total and those related to treatment, respectively [16][17][18][19][20][21][22][23][24][25].…”
Section: Ppi -Proton Pump Inhibitor Re -Reflux Esophagitis Od -Once D...mentioning
confidence: 99%